CHALLENGES OF ONLINE LEARNING DURING PANDEMIC COVID-19 IN JUNIOR HIGH SCHOOL - Ermawati Ermawati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2023)
Coronavirus has moved people's learning patterns from the classroom to the internet. This article explores the challenges of online learning during the pandemic: hardware and internet connectivity concerns, perspectives of student, teacher and parent, and school system. Interview was used to collect the data. The descriptive analysis was implemented to categorize and classify the claims. It is discovered that certain students do not have a smartphone, that internet data is costly, and that the network is bad based on hardware and internet access. Students' perspectives on online learning include making a lot of tasks, difficult-to-understand content, being unable to access the internet, and not being able to use any phone apps. The viewpoints of the teachers are also listed. They include a lack of IT comprehension, a poor connection, a lack of student answers, and a loss of direct contact. Other experiences shared by parents include the inability to afford internet data, a lack of expertise, and inadequate time to assist their children in online learning, and the parents' complaint about their children's online gaming distraction. The education system, which dictates the lack of IT preparation and the minimal budget for promoting online learning, is the final challenge. The results suggest that teachers, parents, and schools should exert greater control over the development of online learning for students.